Preparation and fracture behavior of bionic layered SiCp/Al composites by tape casting and pressure infiltration. Issue 6 (15th March 2023) - Zhao, Qiqi; Ju, Boyu; Guo, Tingting; Yang, Wenshu; Kang, Pengchao; Xue, Wei; Liu, Hao; Xiu, Ziyang; Chen, Guoqin; Jiang, Longtao; Wu, Gaohui
Abstract: In this study, the bioinspired laminated composites with alternating soft Al layers and hard SiCp/Al were fabricated through the tape casting followed by pressure infiltration. In-situ bending and digital image correlation technology (DIC) analysis were carried out on the laminated composites. The results showed that the uniform layers of SiCp/Al and Al were obtained with the thickness of 30 μm and 10 μm, respectively. The interfaces between layers had an intimated combination. The bending deformation process of the laminated composites could be divided into three stages, i.e., crack initiation, crack stable diffusion and crack propagation instability. During deformation, the laminated structure changed the state of strain and strain distribution, further restricted the development of the crack, and the whole materials presented a stepped fracture. This study provides support for preparation and fracture process analysis of biomimetic layered composites prepared by tape casting.